Manajemen Administrasi Sekolah menuju Standardisasi Sekolah Ramah Anak: Studi Kasus SD Fransiskus Kalirejo - Piter Agung Dwi Nugroho; Tri Yuni Hendrowati; Fatqul Hajar Aswad; Siswoyo Siswoyo (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze how school administrative management through the POAC (Planning, Organizing, Actuating, Controlling) function can support the standardization process of Child-Friendly Schools (SRA) at Fransiskus Elementary School, Kalirejo, Central Lampung. The research method used was a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation studies. Data were then analyzed using the interactive model of Miles, Huberman, and Saldana. The results showed that the implementation of the planning function was aligned with the school's vision and mission and SRA regulations. Organization was carried out through the formation of a decree-based SRA Team structure with a clear division of roles. Implementation (actuation) was characterized by instructional leadership and positive discipline, as well as stakeholder involvement. Controlling was carried out through participatory audits, supervision based on child-friendly indicators, and an effective complaint system. Overall, POAC-based administrative management proved to be a key foundation for the institutionalization of SRA, although challenges remain in the digitalization of administration. The conclusion of this study is that the success of Child-Friendly School standardization is largely determined by the strength of an integrated, adaptive, and child-protection-based school administration system, which needs to be strengthened through digitalization and system enhancements that are not dependent on individuals.                                       Keywords: School Administration, Management, Child-Friendly Schools, Standardization